2012
DOI: 10.1108/17506181211233036
|View full text |Cite
|
Sign up to set email alerts
|

Island tourism: destinations: an editorial introduction to the special issue

Abstract: PurposeThis editorial aims to situate the papers chosen for this special issue within academic literature and identify their contributions to new knowledge.Design/methodology/approachThe editorial first discusses tourism research literature pertinent to the idiosyncrasies of destination management in island contexts. Second, the paper identifies the contributions made to this field by the authors and the implications of their innovative research for island tourism and destination management.FindingsEach paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 111 publications
(96 reference statements)
1
15
0
1
Order By: Relevance
“…This observation concurs with an earlier observation by Cave and Brown (2012), who argue that, away from centres of governance, regulatory mechanisms, and infrastructure planning, tourism operators and tourists do not utilise tourism resources responsibly. Regarding the visiting time, it was found that most visitors spent an average of 4-5 hours on the islet, whereas in a few cases, groups of people stayed overnight for camping purposes.…”
Section: Ilot Bernaches As a Tourism Isletsupporting
confidence: 79%
See 2 more Smart Citations
“…This observation concurs with an earlier observation by Cave and Brown (2012), who argue that, away from centres of governance, regulatory mechanisms, and infrastructure planning, tourism operators and tourists do not utilise tourism resources responsibly. Regarding the visiting time, it was found that most visitors spent an average of 4-5 hours on the islet, whereas in a few cases, groups of people stayed overnight for camping purposes.…”
Section: Ilot Bernaches As a Tourism Isletsupporting
confidence: 79%
“…The study by Cave and Brown (2012) (Ioannides, 2008), environmental audit (Diamantis& Westlake, 1997) on the Greek island of Mytilini; destination knowledge mapping in Korea (Pyo, 2005); the tourism consumption system (Woodside & Dubelaar, 2002); integrated technical economic modelling (Xu et al, 2003); and systems approaches that encompass multiple social, economic, cultural, and environmental dimensions (Carlsen, 1999;Northcote & Macbeth, 2006). These models are obviously underpinned by an awareness that tourism deals with finite-rather than infinitely renewable-markets and resources, leading to the need for sustainable approaches in the management of island destinations (Dodds, 2007).…”
Section: Destination Management Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, islands, in part because of their insularity, often house fragile environments and rare wildlife, as well as unique cultural features (Baum, 1997;González-Morales et al, 2016). The biophysical attributes and institutional specificities of insularity are often associated with distinctive natural and cultural features, creating an 'island allure' that may be appealing to those from the mainland (Baldacchino, 2004;Cave & Brown, 2012;Grydehøj, 2017;Petridis et al, 2017). Islandness, as an expression of the complex identity or sense of place of islands (Stratford, 2008), encompasses a state of tension between "openness and closure" (Baldacchino, 2004, p. 274), and may open up novel political, socioeconomic, and ecological possibilities, which may have development potential (Petridis et al, 2017).…”
Section: Island Tourism and Yujiale Operation In Chinamentioning
confidence: 99%
“…And yet, there is still a lot to be learnt about these insular spaces. Some argue that by comprehending island environments one can understand larger and more complex systems (Bergstrom et al, 2009) and that changes experienced on islands can anticipate phenomena that will eventually occur elsewhere (Cave and Brown, 2012;Essex et al, 2004). Baldacchino (2007) suggests that oceanic islands in particular 'are useful systems for understanding human-land interactions .…”
mentioning
confidence: 99%